2021
DOI: 10.1371/journal.pmed.1003468
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal psychotherapy delivered by nonspecialists for depression and posttraumatic stress disorder among Kenyan HIV–positive women affected by gender-based violence: Randomized controlled trial

Abstract: Background HIV–positive women suffer a high burden of mental disorders due in part to gender-based violence (GBV). Comorbid depression and posttraumatic stress disorder (PTSD) are typical psychiatric consequences of GBV. Despite attention to the HIV-GBV syndemic, few HIV clinics offer formal mental healthcare. This problem is acute in sub-Saharan Africa, where the world’s majority of HIV–positive women live and prevalence of GBV is high. Methods and findings We conducted a randomized controlled trial at an H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 39 publications
(51 reference statements)
3
31
0
Order By: Relevance
“…A pilot trial in Egypt among Sudanese refugees reported decreased depression and PTS symptoms among its participants [ 41 ]. There is additional evidence that supports efficacy among GBV survivors—an RCT in Kenya among HIV-positive women affected by GBV reported support for both the content and structure of a group IPT intervention, as well as its feasibility [ 42 , 43 ]. Given its effectiveness in treating depression, the WHO has released an adapted and translated manual for group IPT, and recommend it as a “first-line” treatment for depression [ 44 ].…”
Section: Results: Psychological Intervention Modalitiesmentioning
confidence: 99%
“…A pilot trial in Egypt among Sudanese refugees reported decreased depression and PTS symptoms among its participants [ 41 ]. There is additional evidence that supports efficacy among GBV survivors—an RCT in Kenya among HIV-positive women affected by GBV reported support for both the content and structure of a group IPT intervention, as well as its feasibility [ 42 , 43 ]. Given its effectiveness in treating depression, the WHO has released an adapted and translated manual for group IPT, and recommend it as a “first-line” treatment for depression [ 44 ].…”
Section: Results: Psychological Intervention Modalitiesmentioning
confidence: 99%
“…We reviewed the full text of 287 potentially eligible studies and excluded 272 studies (Appendix S2 in the Online Supplementary Document ). We ultimately included 15 studies [ 14 - 16 , 21 - 32 ] which corresponded to 14 RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Four trials were pilot studies [ 21 , 23 , 27 , 28 ]. There were eleven parallel RCTs [ 14 - 16 , 21 , 26 - 32 ], one stepped-wedge RCT [ 22 ], one full factorial RCT [ 23 ], one three-arm RCT [ 25 ]. Six studies were conducted in China [ 14 , 21 , 25 , 26 , 30 , 31 ], two in South Africa [ 16 , 28 ], one in Tanzania [ 22 ], one in Argentina [ 23 ], one in Uganda [ 15 ], one in India [ 27 ] and two in Kenya [ 29 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meffert et al . ( 2021 ). b Electronic Medical Records (EMR) in public sector primary care are robust in many SSA regions, partly associated with the implementation of the continuum of HIV care (Haskew et al ., 2015 ; Kang'a et al ., 2017 ).…”
Section: Discussionmentioning
confidence: 99%